Pinch Anatomy of Forehead: An Injection Guide for Forehead Filler Treatment - Kapoor, Krishan M.; Chatrath, Vandana; Li, Chris Q.; Bertossi, Dario (Facial Plastic Surgery, 2022)
Filler injections have become very popular in recent years, and injectors globally use them for facial shaping and reversing age-related changes. Detailed knowledge about important vessels' and tissue planes' anatomy is essential for injectors. While giving the filler injections, injectors tend to gently pinch or pull the tissue fold with the nondominant hand during the procedure. The deformational forces cause some changes in the anatomy of tissue layers held in a pinch. During the pinch and “pinch and pull” maneuver, the crucial vessels in the area can get pulled up in the tissue layers in a pinch or stay in their position unaffected depending on the force applied. The “pinch and pull” maneuver also increases the tissue space for injections by moving the mobile tissue layers away from the fixed ones. The injector can use knowledge of the “‘pinch anatomy” in the forehead to avoid important arteries and place filler in the correct plane. With the understanding of the anatomical changes occurring during the pinched state of tissue layers, filler injection can be performed in the right and safer tissue plane in the forehead. This study reflects level of evidence V.
Keywords: pinch anatomy; fillers; dermal filler; filler injection; facial anatomy; injection anatomy; hyaluronic acid; filler complications; filler technique; forehead fillers